Comparison of Heart Rate Variability among Young Malay Male Adult with Different BMI and Level of Adiposity - Juliana, N; Nadia, ME; Roslan, NA; Ghazali, AR; Fauzi, NFM; Sahar, MA; Sulaiman, AH; Hayati, A; Mohamed, AL (Int Islamic Univ Malaysia, Kulliyyah Medicine, 2024)
Indexed by WOS/Scopus